The Association Between Illness Acceptance and Quality of Life in Women with Breast Cancer - Jankowska-Polańska, Beata (Cancer Manag Res, 2020)
INTRODUCTION: Breast cancer is the most common cause of cancer death in women. AIM: The aim of the study was to investigate the association between illness acceptance and quality of life (QoL) in patients with breast cancer. PATIENTS AND METHODS: The study included 150 patients who had undergone surgery for breast cancer. The following standardized questionnaires were used: the Acceptance of Illness Scale (AIS), the EORT QLQ–C30 (The European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30), and the EORT QL–BR 23 (Quality of Life Questionnaire for Breast Cancer) for QoL evaluation. Socio-clinical data were obtained from the patients’ medical records. RESULTS: In the study group, the overall QoL score was 62.67±17.11 in the BCT group, 63±14.3 in the MTX group, and the highest: 65.5±20.2 in the reconstruction group. Comparative analysis showed that patients in the BCT group reported significantly more fatigue (p=0.007) and appetite loss (p=0.032) than those in the MTX+R group. Patients in the MTX group were significantly less satisfied with their body image (p=0.001) and experienced more financial troubles (p=0.013) than the remaining patients. Patients in the MTX+R group reported significantly better sexual function and more sexual enjoyment than the remaining patients (p<0.001). All patients scored high for illness acceptance, though patients in the MTX group had lower scores (28.17±7.2) than the others: 31.84±6.51 in the BCT group and 32.78±7.97 in the MTX+R group. The comparative analysis of QoL according to the level of AIS showed the significantly better QoL and less intense symptoms within all the domains except for the insomnia and hair loss domains in the group of high AIS in comparison with medium and lack of AIS. Acceptance of illness significantly correlated with 4 domains of the QLQ-C30 (p<0.05). The correlation between illness acceptance and overall QoL was positive (r=0.243; p=0.003) – the higher the acceptance, the better the QoL. Correlations with pain, diarrhoea, and financial difficulties were negative. Illness acceptance was positively correlated with QoL in 3 domains of the EORTC–BR23: body image (p<0.001), sexual function (p=0.015), and sexual enjoyment (p=0.047), and negatively with the “treatment side effects” (p=0.011). CONCLUSION: The level of illness acceptance varies depending on the treatment method, and is the lowest in the group of women having undergone a mastectomy, and the highest in patients after a mastectomy with immediate breast reconstruction. Acceptance of illness improves the QoL of women treated for breast cancer, regardless of the specific treatment method.